METODOLOGI PENULISAN SYEKH ‘ABD AL-HAY AL-LAKNAWI DALAM KITAB ZAFAR AL-AMANI - Mohd. Khafidz Soroni (Universitas Ahmad Dahlan, 2021)
Throughout the history of the tradition of Islamic studies, there have been various works of ‘ulum al-hadith that have been produced by hadith scholars. These works differ in their writing methodology from one work to another. To understand the differences, a study of each work and the background of the author is very necessary to be conducted to reveal and explain it. Thus, this study aims to introduce one of the figures in the discipline of ‘ulum al-hadith named Sheikh ‘Abd al-Hay al-Laknawi (d. 1304H) with a focus on one of his monumental works, namely Zafar al-Amani fi Sharh Mukhtasar al-Jurjani. This qualitative study uses content analysis methods to identify and comprehensively describe the methodology of al-Laknawi's writing in the work. From the results of the study it can be concluded that the methodology of writing al-Laknawi is seen as quite systematic and loaded with scientific discussions on issues that are quite complex in the science of hadith such as the issue of hadith hasan, the problem of doing good deeds with weak hadith, the issue of hadith mursal, issues munkar hadith and so on, along with his interpretation of the various views of the scholars presented. According to the research, this book of Zafar al-Amani is quite worthy to be placed in line with the great works of the discipline of ‘ulum al-hadith which should be studied and used as a reference by scholars and students.